Historical HbA1c values may explain the type 2 diabetes legacy effect: UKPDS 88 - Lind, M; Imberg, H; Coleman, RL; Nerman, O; Holman, RR (American Diabetes Association, 2021)
Type 2 diabetes all-cause mortality (ACM) and myocardial infarction (MI) glycemic legacy effects have not been explained. We examined their relationships with prior individual HbA1c values and explored the potential impact of instituting earlier, compared with delayed, glucose-lowering therapy. Twenty-year ACM and MI hazard functions were estimated from diagnosis of type 2 diabetes in 3,802 UK Prospective Diabetes Study participants. Impact of HbA1c values over time was analyzed by weighting them according to their influence on downstream ACM and MI risks. Hazard ratios for a one percentage unit higher HbA1c for ACM were 1.08 (95% CI 1.07-1.09), 1.18 (1.15-1.21), and 1.36 (1.30-1.42) at 5, 10, and 20 years, respectively, and for MI was 1.13 (1.11-1.15) at 5 years, increasing to 1.31 (1.25-1.36) at 20 years. Imposing a one percentage unit lower HbA1c from diagnosis generated an 18.8% (95% CI 21.1-16.0) ACM risk reduction 10-15 years later, whereas delaying this reduction until 10 years after diagnosis showed a sevenfold lower 2.7% (3.1-2.3) risk reduction. Corresponding MI risk reductions were 19.7% (22.4-16.5) when lowering HbA1c at diagnosis, and threefold lower 6.5% (7.4-5.3%) when imposed 10 years later. The glycemic legacy effects seen in type 2 diabetes are explained largely by historical HbA1c values having a greater impact than recent values on clinical outcomes. Early detection of diabetes and intensive glucose control from the time of diagnosis is essential to maximize reduction of the long-term risk of glycemic complications.